Fabrication of Aromatic Polyimide Membrane to Study the Pervaporative Separation of Phenanthrene/n-tetradecane Mixtures (Model Diesel) and Process Optimization Using Response Surface Methodology. Issue 1 (2nd January 2017) - Roychowdhury, Sayan; Mitra, Debarati
Abstract : To meet stringent fuel specifications, separation of aromatics from aliphatics is an everyday challenge for a refiner. In the present investigation, an aromatic polyimide membrane is fabricated and explored for the separation of a polyaromatic hydrocarbon (phenanthrene) from a model diesel composition (n-tetradecane) via pervaporation. The pervaporative membrane is prepared by casting a solution of polyamic acid, N, N-dimethylacetamide (DMAc), and phenanthrene using a simple and low-cost procedure. Scanning electron microscopy (SEM), Fourier transform infrared spectrometry (FTIR), and swelling in feed solution of the synthesized membrane have been conducted for its characterization. The membrane allows preferential permeation of phenanthrene. The influence of different physico-chemical parameters, on permeation flux and enrichment factor for n-tetradecane/phenanthrene mixtures, has been studied. Statistical software Design Expert 7.1.4 is used to derive the regression equation, which describes the effect of time, downstream pressure, feed solute concentration, and operating temperature on the Pervaporation Separation Index (PSI). These factors are optimized using response surface methodology (RSM). The highest value of the PSI obtained is 0.623 kg m −2 h −1 and the corresponding optimized condition is: operating time is 11.58 h, the feed solute concentration is 162.96 ppm with a downstream pressure of 0.58 mm of Hg and an operating temperature of 449.03 K.